The TEXTOR diagnostic data management chain - Krom, J.G.; Korten, M.; Koslowski, H.R.; Krämer-Flecken, A. (Fusion engineering and design, 2005)
During the 2002–2003 shutdown of TEXTOR, many components of the TEXTOR diagnostic data management system were upgraded. This paper intents to give an overview of these upgraded components and how they co-operate to form one integrated Data Management System. The components in question are: (1) JDAQ: The Java (or Juelich) Data Acquisition System, a newly created data acquisition system, completely written in the JAVA object oriented programming language. (2) The TEC Common Storage Facility and the Textor Physics Database. (3) The TEC Web-Umbrella: A unified data access scheme based on the widely used HTTP protocol. (4) Chainl: A framework for automatically run chains of analysis software.